54th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2013
DOI: 10.2514/6.2013-1559
|View full text |Cite
|
Sign up to set email alerts
|

Post-Critical Analysis of Joined Wings: the Concept of Snap-Divergence as a Characterization of the Instability

Abstract: The concept of snap divergence and post-critical states are theoretically formulated for Joined Wings with the arc length technique. The true critical condition is compared with the divergence speed evaluated by solving an eigenvalue problem about a steady state equilibrium, showing how in some cases this last approach is not reliable and even nonconservative.The work assesses the difference of the nonlinear responses relative to mechanical loads (both conservative and follower ones) used to mimic the real loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 29 publications
(69 reference statements)
1
23
0
Order By: Relevance
“…In the present effort the magnitude is considered to be constant and the reference followed direction is parallel the normal to an element vector. In reference [60] a case in which the magnitude only depends on the deformation. Before further proceeding, in the following of this contribution, the terms array and vector are differently used: when referring to the Euclidean space the terminology vector is used, whereas, referring to finite element degree of freedoms space the word array is employed.…”
Section: Definition Of Follower Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present effort the magnitude is considered to be constant and the reference followed direction is parallel the normal to an element vector. In reference [60] a case in which the magnitude only depends on the deformation. Before further proceeding, in the following of this contribution, the terms array and vector are differently used: when referring to the Euclidean space the terminology vector is used, whereas, referring to finite element degree of freedoms space the word array is employed.…”
Section: Definition Of Follower Forcesmentioning
confidence: 99%
“…Not only could linear analysis tools be strongly nonconservative, recommending the employment of expensive nonlinear tools (see [27,60]). But it is also suggested that, for static analysis the post-critical branch should be pursued in order to assess the existence of different static equilibrium points for the same load level (speed).…”
Section: A Branch-jumping For Conservative Loadingmentioning
confidence: 99%
“…The numerical investigations presented in references [4,5,11,13,16] characterized the response of Joined Wings on a conceptual level. In particular, a snap-instability was first found when statically loading the structure with mechanical forces.…”
Section: Contribution Of the Present Studymentioning
confidence: 99%
“…In reference [13] the snap-divergence was compared to the traditional divergence analysis, performed through an eigenvalue analysis about particular configurations (usually the undeformed one). Discrepancy between the critical speeds predicted by these two approaches was substantial.…”
Section: Contribution Of the Present Studymentioning
confidence: 99%
See 1 more Smart Citation